Janus kinase 2: a novel negative regulator of estrogen receptor α function - Gupta, Nibedita; Grebhardt, Sina; Mayer, Doris (Cellular signalling, 2012)
Estrogen receptor α (ERα) functions as a transcription factor to regulate a wide range of cellular activities in response to 17β-estradiol (E2). The regulation of ERα transcriptional activity is highly complex and not yet fully understood. In this respect, recent studies have highlighted the importance of certain cellular protein kinases. To identify novel protein kinases regulating ERα activity, we performed a high-throughput siRNA screening in combination with a luciferase reporter assay in an ERα positive breast cancer cell line. Among the vast majority of potential positive regulators, we found Janus kinase 2 (JAK2), a member of the Janus kinase family of non-receptor tyrosine kinases, to have a negative regulatory effect on E2 induced luciferase activity. In addition, silencing of JAK2 resulted in increased expression of endogenous ERα target genes, pS2 and GREB1. In an attempt to understand the mechanism underlying JAK2 mediated regulation of ERα transcriptional activity, we found that JAK2 negatively regulates ERα protein level. Gene expression analysis revealed no significant influence of JAK2 on ERα mRNA level. Subsequently, a role of JAK2 in regulating ERα protein degradation was analyzed. Inhibition of the lysosome did not alter JAK2 mediated downregulation of ERα. In contrast, using proteasome inhibitors MG132 and lactacystin, we demonstrated that JAK2 governs ERα protein stability via the ubiquitin-proteasome pathway. In contrast to JAK2, the two other members of the JAK family expressed in the breast (JAK1 and TYK2) had no influence on ERα function. In addition, we found that prolonged E2 treatment upregulates JAK2 mRNA and protein levels. These results suggest a novel negative regulation of ERα activity and protein by JAK2 in breast cancer cells and indicate a potential new cross-talk.